EFEKTIFITAS TERAPI MUSIK KLASIK MOZART TERHADAP SUHU TUBUH BAYI PREMATUR DI RUANG PERINATOLOGI RSUD BANGKINANG - Nila Kusumawati (Universitas Pahlawan, 2018)
Premature babies, some of their organs, cannot function properly. One problem that often occurs in premature babies is instability in body temperature. Premature babies often experience hypothermia. Mozart's classical music therapy is one of the therapeutic music that helps overcome temperature instability in premature babies. This study aims to determine the effectiveness of Mozart's classical music therapy on the body temperature of premature babies in the Perinatology Room of Bangkinang Hospital. This study uses a quasy experiment design with a non-randomized control group pretest-posttest design approach. Sampling using purposive sampling technique. The number of samples in this study were 30 premature babies consisting of 15 premature babies for the experimental group and 15 premature infants for the control group. Analysis of the data used is the t test. The results of this study were no differences in body temperature of premature infants before being given Mozart classical music therapy in the control group and experimental group (p value = 0.119). There were significant differences in body temperature of premature babies before and after being given Mozart classical music therapy in the experimental group (p value = 0,000) and there was no difference before and after being given Mozart classical music therapy in the control group (p value = 0.119). There was a difference in body temperature of premature infants after being given Mozart classical music therapy in the experimental group and the control group (p value = 0,000). The conclusion of this study is the provision of Mozart's classical music therapy. Premature babies are more effective at stabilizing temperatures in premature babies so it is recommended to provide Mozart classical music therapy in premature babies.